2017
DOI: 10.5455/njppp.2017.7.0622130062017
|View full text |Cite
|
Sign up to set email alerts
|

Physiological cost index of different body mass index and age of an individual

Abstract: Background:The energy expenditure is the amount of energy (or calories) that a person needs to carry out a physical function such as breathing, circulating blood, digesting food, or a physical movement. The method for estimating the energy cost using measurement of heart rate (HR) is the physiological cost index (PCI). Aims and Objective: The aim of this study is to measure and correlate the relationship of energy expenditure of a normal healthy individual with different body mass index (BMI) and age. Material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…It is observed that as the BMI increases, the physiological cost index increases, thus concluding more energy expenditure. (2) Hence our study is undertaken to improve the physiological cost index of obese individuals by giving aerobic exercise.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is observed that as the BMI increases, the physiological cost index increases, thus concluding more energy expenditure. (2) Hence our study is undertaken to improve the physiological cost index of obese individuals by giving aerobic exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Energy expenditure varies with both among individual and within the same person depending on the circumstance, body weight, walking speed, surface texture and gradient. (2) The PCI is an easy to use valid and reliable measure of energy expenditure and it is recommended as a useful tool for physiotherapist in the assessment and evaluation of functional performance. The PCI was founded on the principle that Heart rate (HR) and walking speed are linearly related to VO2 at the submaximal levels of exercise.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Energy is expended by individuals engaging in physical activity 1 . The energy expenditure is the amount of energy or calories that a person needs to carry out a physical function such as breathing, circulating blood, digesting food or a physical movement 3 . Energy expenditure index based on heart rate and walking speed has been termed Physiological Cost Index (PCI) by McGregor.…”
Section: Introductionmentioning
confidence: 99%